Isochroman- and 1,3-dihydroisobenzofuran-annulation on carbohydrate templates via [2+2+2]-cyclotrimerization and synthesis of some tricyclic nucleosides - Suryawanshi, Sharad B.; Dushing, Mangesh P.; Gonnade, Rajesh G.; Ramana, C. V. (Tetrahedron, 2010)
The synthesis of enantiopure tricyclic systems comprising isochroman or dihydroisobenzofuran units integrated with sugar templates has been documented. The alkyne cylotrimerization reaction has been employed with easily accessible sugar diynes for the key bicyclic ring construction and thus a provision to alter the functional groups on the newly formed aromatic rings. By selecting two representative trimerization products, we have synthesized the tricyclic nucleosides by simple synthetic manipulations. (c) 2010 Elsevier Ltd. All rights reserved.
Keywords: Dihydroisobenzofuran; Dihydroisobenzopyran; Modified nucleosides; Vorbruggen reaction; [2+2+2] cyclotrimerization

Target cum flexibility: synthesis of indolo[1,2-b]isoquinoline derivatives via cobalt-catalyzed [2+2+2] cyclotrimerization - Swami, Anuradha; Ramana, Chepuri V. (Synlett, 2015)
A modular approach for the synthesis of small molecules having the unnatural 6,11-dihydroindolo[1,2-b]isoquinoline tetracyclic core has been documented. An acid-catalyzed Friedel-Crafts-type C2-alkylation of N-propargyl indole with a suitably activated alkynol has been used to prepare the key indole-derived diynes. The cobalt-catalyzed [2+2+2] cyclotrimerization of these diynes has been studied with various internal/terminal alkynes and with nitriles.
Keywords: 2-b]-isoquinoline; cobalt; Indole; indolo[1; Pyridine; [2+2+2] cyclotrimerization